An inventory and routing model using deterministic and stochastic demand. - Belfiore, Patrícia Prado; Costa, Oswaldo Luiz do Valle; Fávero, Luiz Paulo Lopes (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper analyses the inventory routing problem, which is an extension of the traditional vehicle routing problem. The objective is to develop a problem modeling and to create a methodology of solution based on a hierarchical decision model. The problem consists in determining when and how much merchandise needs to be delivered to each customer and which delivery routes can be used; the target is to minimize the inventory and distribution costs, so that the customer´s demands can be attended. Keywords: Inventory; Routing; Deterministic demand; Stochastic demand.